The Influence of Computer Self-Efficacy and Computer Anxiety on Students Interest in Operating Accounting Software with Basic Accounting Understanding as a Moderator: - Ade Hyang Vanariz Kirana; Ria Mennita (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The study addresses the issue of student’s interest in operating accounting software being hindered by computer anxiety and low computer self-efficacy, particularly among accounting students facing digital transformation in education. The aim is to analyze the influence of computer self-efficacy and computer anxiety on students’ interest in using accounting software, with basic accounting understanding as a moderating factor. The research employs a quantitative method using questionnaires distributed to 147 students from the 2022-2023 batches at Merdeka Malang University. Results show that computer self-efficacy positively affects interest, while computer anxiety has a negative impact, and basic accounting understanding moderates these relationships by strengthening the positive effects and mitigating the negative ones. In conclusion, enhancing self-efficacy and reducing anxiety through targeted educational strategies can boost students’ interest in accounting software.